Effect of ageing on the properties and polycyclic aromatic hydrocarbon composition of biochar. Issue 5 (3rd May 2017) - Sigmund, Gabriel; Bucheli, Thomas D.; Hilber, Isabel; Micić, Vesna; Kah, Melanie; Hofmann, Thilo
Abstract : Biochar field ageing changed PAH composition, generally decreased PAH leaching, and could not be simulated by lab ageing. Abstract : The influence of ageing on biochar properties has been investigated by comparing three fresh biochars with biochars artificially aged by either H2 O2 thermal oxidation or horseradish peroxidase enzymatic oxidation. In addition, a field-aged counterpart for one of the biochars was recovered from an agricultural field site, four years after application. Biochar properties, including surface areas and pore volumes (derived by N2 and CO2 physisorption) and elemental compositions, showed only minor changes following both artificial and field ageing, indicating high biochar stability. Concentrations of the 16 US EPA PAHs were measured in all of the biochars and a contaminant trap was used to investigate the effect of ageing on their bioaccessibility. The concentrations of total and bioaccessible PAHs ranged from 4.4 to 22.6 mg kg −1 and 0.0 to 9.7 mg kg −1, respectively. Concentrations of the 16 US EPA PAHs decreased following field ageing, but the proportion of low molecular weight PAHs increased. The observed changes in PAH composition with field ageing can be explained by uptake from the surrounding soil and intra-biochar transfer processes. To better understand changes in PAH composition with ageing, an additional broad range of alkylated PAHs was also analyzed in selected samples. Our results show that the tested artificial ageing protocols are unable to approximate the changes in PAH composition resulting from field ageing. Nevertheless, total and bioaccessible PAH concentrations decreased for both artificially and field-aged biochars, indicating that biochars release PAHs when they are freshly produced and that the risk of PAH release decreases with ageing.